Предмет: Математика,
автор: madinadj1
Упростите выражения : (-a)*b*(-a)*b*(-a)
8m*(-n)*(-m)*2n
(-ab)*(-bc)*(-ca)
(-2ху)*(-2yz)*(-2xz)*(-2xyz)
Помогите плиз
74 балла
Ответы
Автор ответа:
0
(-a)*b*(-a)*b*(-a) = -а³b²
8m*(-n)*(-m)*2n = 16m²n²
(-ab)*(-bc)*(-ca) = - a²b²c²
(-2ху)*(-2yz)*(-2xz)*(-2xyz) = 16х³у³z³
8m*(-n)*(-m)*2n = 16m²n²
(-ab)*(-bc)*(-ca) = - a²b²c²
(-2ху)*(-2yz)*(-2xz)*(-2xyz) = 16х³у³z³
Похожие вопросы
Предмет: История,
автор: llolololoooll
Предмет: Русский язык,
автор: vikaroma92
Предмет: Русский язык,
автор: alina234848
Предмет: Литература,
автор: kirilinagalina
Предмет: Биология,
автор: nascenachka